The Role of NFκB in Healthy and Preeclamptic Placenta: Trophoblasts in the Spotlight - Armistead, Brooke (Int J Mol Sci, 2020)
The NFκB protein family regulates numerous pathways within the cell—including inflammation, hypoxia, angiogenesis and oxidative stress—all of which are implicated in placental development. The placenta is a critical organ that develops during pregnancy that primarily functions to supply and transport the nutrients required for fetal growth and development. Abnormal placental development can be observed in numerous disorders during pregnancy, including fetal growth restriction, miscarriage, and preeclampsia (PE). NFκB is highly expressed in the placentas of women with PE, however its contributions to the syndrome are not fully understood. In this review we discuss the molecular actions and related pathways of NFκB in the placenta and highlight areas of research that need attention